N-(2-Methoxy-ethyl)phthalimide - Sim, Y.L.; Ariffin, A.; Ng, Seik Weng (International Union of Crystallography, 2008)
The title mol-ecule, C(11)H(11)NO(3), lies on a crystallographic mirror plane which bis-ects the plane of the phthalimide unit and contains the C and O atoms of the 2-methoxy-ethyl group.